Can Local Stress Enhancement Induce Stability in Fracture Processes? Part I: Apparent Stability - Kjellstadli, Jonas T.; Bering, Eivind; Hendrick, Martin; Pradhan, Srutarshi; Hansen, Alex (Frontiers in Physics, 2019)
By comparing the evolution of the local and equal load sharing fiber bundle models, we point out the paradoxical result that stresses seem to make the local load sharing model stable when the equal load sharing model is not. We explain this behavior by demonstrating that it is only an apparent stability in the local load sharing model, which originates from a statistical effect due to sample averaging. Even though we use the fiber bundle model to demonstrate the apparent stability, we argue that it is a more general feature of fracture processes.